PBQP-H e Norma de Desempenho: um estudo de múltiplos casos com micro e pequenas construtoras cearenses - Maciel, Francisco Wandisley Freitas; Cândido, Luís Felipe; Rocha, Virna Fernandes Távora (SIMPÓSIO BRASILEIRO DE GESTÃO E ECONOMIA DA CONSTRUÇÃO, 2021)
This paper aims to analyze the implementation of PBQP-H and the Brazilian standard of performance to residential building (ABNT NBR 15.575) in small business of construction sector. This can help to understand the status of implementation of these two milestones of quality improvement for the building construction sector in Brazil, due to the lack of studies focused on this specific sector. Through multiple case study, improvements in the internal process were identified, evidencing the positive contributions of PBQP-H to achieve the performance required by the ABNT NBR 15.575. The interviewed also quoted positive impacts such as cost saving, time reducing and benefits to customers and end users. Finally, the study conclude that the low adherence of PQBP-H is still related to the poor view of managers, who interpret investments in quality only as certification costs.